Eemian landscape response to climatic shifts and evidence for northerly Neanderthal occupation at a palaeolake margin in northern Germany. Issue 14 (14th September 2021) - Hein, Michael; Urban, Brigitte; Tanner, David Colin; Buness, Anton Hermann; Tucci, Mario; Hoelzmann, Philipp; Dietel, Sabine; Kaniecki, Marie; Schultz, Jonathan; Kasper, Thomas; von Suchodoletz, Hans; Schwalb, Antje; et al.
Abstract: The prevailing view suggests that the Eemian interglacial on the European Plain was characterized by largely negligible geomorphic activity beyond the coastal areas. However, systematic geomorphological studies are sparse. Here we present a detailed reconstruction of Eemian to Early Weichselian landscape evolution in the vicinity of a small fingerlake on the northern margin of the Salzwedel Palaeolake in Lower Saxony (Germany). We apply a combination of seismics, sediment coring, pollen analysis and luminescence dating on a complex sequence of colluvial, paludal and lacustrine sediments. Results suggest two pronounced phases of geomorphic activity, directly before the onset and at the end of the Eemian period, with an intermediate period of pronounced landscape stability. The dynamic phases were largely driven by incomplete vegetation cover, but likely accentuated by fluvial incision in the neighbouring Elbe Valley. Furthermore, we discovered Neanderthal occupation at the lakeshore during Eemian pollen zone (PZ) E IV, which is chronologically in line with other known Eemian sites of central Europe. Our highly‐resolved spatio‐temporal data substantially contribute to the understanding of climate‐induced geomorphic processes throughout and directly after the last interglacial period. It helps unraveling the landscape dynamics between the coastal areas to the north and the loess belt to the south. Abstract : Two phases of channel incision at the Saalian‐Eemian transition and in the late Eemian. Incisions closely followed by rising water tables. Long‐lasting phase of geomorphic stability in the mid‐Eemian, characterized by: very dense forest cover. the formation of a fingerlake within the paleochannel with gradually sinking water table. no influx of clastic sediments, but deposition of peat and lake‐marl deposits.